HOTS-Based Pocketbook Development Using QR Scan - Salsabila Karina Manik; Suci Dahlya Narpila (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
The purpose of this study is to develop a HOTS-based pocketbook using QR scans to create student-friendly learning media. The effectiveness of the products developed makes development research activities meaningful. This type of research uses R&D (Research and Development) research or development research using the ADDIE model developed by Dick and Carry. This ADDIE model has five stages, namely, analysis, design, development, application, and evaluation. The subjects of the study were material experts, media experts, teachers, observers, and XI Science 1 students at MAN 1 Medan, totaling 30 students. Data collection techniques in this study are in the form of questionnaires and post-tests. Initially, the researcher designed the book, then made it until it reached the evaluation stage. The results showed that the percentage value of media experts was 84% and the results of material expert validation were 88% with very feasible criteria. While the practicality value is 93.33% with very practical criteria. The effectiveness value of this study was 76.83% with effective criteria. Keywords: pocketbook, QR scans, HOTS